EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN JAGUNG (ZEA MAYS L) DI KECAMATAN WANGGARASI KABUPATEN POHUWATO - Hasan, Yusrin; Arief Azis, Muhammad; Rahim, Yunnita; Nurmi; Rahman, Rival (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2024)
This study aims to determine land suitability classes and limiting factors for corrn crops in Wanggarasi Sub-District. This research was conducted in Wanggarasi Sub-District, Pohuwato Regency from September to December 2022. This research uses the matching method between the characteristics and quality of land in Wanggarasi Sub-District with the characteristics of land suitability for maize (Zea mays L) plans to produce actual and potential land suitability classes. Data processing was carried out by analyzing land characteristics and quality, and land suitability class analysis. The analysis results show that the study area has an actual land suitability class N (unsuitable) and S3 (marginal suitability). With the limiting factors of oxygen availability (drainage conditions), nutrient retention (cation exchange capacity, base saturation, and effective depth), available nutrients (N, P, and K nutrients), slope conditions and erosion hazard. Wanggarasi Sub district has a potential land suitability class S2 (quite suitable) and S3 (Marginally suitable) with a total area of 4730.30 ha.